2021
DOI: 10.13075/ijomeh.1896.01775
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influenza vaccination of healthcare workers: a narrative review

Abstract: Influenza is an acute respiratory disease caused by the influenza virus which often occurs in outbreaks and epidemics worldwide. The World Health Organization recommends annual vaccination of healthcare workers (HCWs) against influenza, because most of them are involved in the direct care of patients with a high risk of influenza-related complications. Given the significance of the disease burden, a targeted literature review was conducted to assess issues related to influenza vaccination among HCWs. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 54 publications
(140 reference statements)
0
10
0
1
Order By: Relevance
“…Furthermore, several studies reported data on presenteeism associated with influenza-like illness (ILI) among HCWs [ 9 , 10 , 11 ]. Results of these studies show that a large group of physicians (even >75% [ 11 ]) admit to carrying out their work despite having flu-like symptoms (the so-called presenteeism).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, several studies reported data on presenteeism associated with influenza-like illness (ILI) among HCWs [ 9 , 10 , 11 ]. Results of these studies show that a large group of physicians (even >75% [ 11 ]) admit to carrying out their work despite having flu-like symptoms (the so-called presenteeism).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies reported data on presenteeism associated with influenza-like illness (ILI) among HCWs [ 9 , 10 , 11 ]. Results of these studies show that a large group of physicians (even >75% [ 11 ]) admit to carrying out their work despite having flu-like symptoms (the so-called presenteeism). For example, according to the results of an American survey (involving 1914 HCWs; influenza season 2014–2015), 41.4% of the respondents reported being present at work with influenza-like symptoms (a median of 3 days), while pharmacists and physicians were the ones who most commonly reported being present at work when sick (67.2% and 63.2%, respectively) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations